2017
DOI: 10.3892/ol.2017.6020
|View full text |Cite
|
Sign up to set email alerts
|

Indolent growth of low-grade myofibroblastic sarcoma of the cheek mimics benign lesions: A case report and literature review

Abstract: Low-grade myofibroblastic sarcoma (LGMS) is a neoplasm of the soft tissue characterized by myofibroblastic differentiation. This type of tumor has been observed in various sites in the whole body, but frequently occurs in the head and neck region. It typically presents as a slow-growing painless mass, which is often mistaken for a benign lesion due to its indolent growth; however, LGMS is a malignant neoplasm. In the present study, a 43-year-old female presented with a 14-mm LGMS lesion in the buccal subcutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…Gadolinium enhancement T1WI showed enhancement of the tumor [ 22 , 41 ]. The border of the tumor on the MRI was varied; some author reported well demarcated tumor [ 7 , 13 , 44 ], but the others were ill-defined [ 10 , 41 , 42 ]. Morii et al [ 41 ] and Niu et al [ 50 ] reported the usefulness of 18 F-Fluorodeoxyglucose-positron emission tomography (FDG-PET)/ computed tomography (CT) for diagnosing LGMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gadolinium enhancement T1WI showed enhancement of the tumor [ 22 , 41 ]. The border of the tumor on the MRI was varied; some author reported well demarcated tumor [ 7 , 13 , 44 ], but the others were ill-defined [ 10 , 41 , 42 ]. Morii et al [ 41 ] and Niu et al [ 50 ] reported the usefulness of 18 F-Fluorodeoxyglucose-positron emission tomography (FDG-PET)/ computed tomography (CT) for diagnosing LGMS.…”
Section: Discussionmentioning
confidence: 99%
“…LGMS is described as a distinct atypical myofibroblastic tumor, often with fibromatosis-like features and predilection for the head and neck [ 2 ]. Oral cavity [ 1 , 3 16 ] and larynx [ 17 20 ] cases are common, but a variety of tissues, including skin [ 21 – 23 ], breast [ 24 , 25 ], vulva [ 26 , 27 ], parapharyngeal space [ 28 ], jaw [ 1 , 10 ], nasal cavity [ 29 ], paranasal sinus [ 29 ], soft tissue of the cheek [ 7 , 23 ], and palate [ 3 , 30 ] have also been reported. LGMS has been characterized as having a low-grade malignant potential, the propensity to recur locally, and a low likelihood of distant metastases [ 1 , 6 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 LGMS is an atypical tumor composed of myofibroblasts, which are spindle-shaped mesenchymal cells present in almost every soft tissue. 3 It presents as a slow-growing, painless mass, and is often mistaken for a benign lesion. LGMS occurs most often in adults and predominantly in men of an average age of 40 years (age range: 9–75 years).…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of LGMS is unknown. This solid infiltrative soft tissue tumor occurs in various sites of the body with a predilection for the head and neck region, particularly the tongue followed by the mandible, neck, larynx, palate, maxilla and lips [ 2 ]. Patients’ mean age is 40 years, but it has been reported in all age groups [ 3 ].…”
Section: Introductionmentioning
confidence: 99%